Genome-wide identification and comprehensive analysis of tubby-like protein gene family in multiple crops - Zeng, Yafei; Wen, Jianyu; Fu, Jinmei; Geng, Han; Dan, Zhiwu; Zhao, Weibo; Xu, Wuwu; Huang, Wenchao (Frontiers in Plant Science, 2022)
The highly conserved tubby-like proteins (TLPs) play key roles in animal neuronal development and plant growth. The abiotic stress tolerance function of TLPs has been widely explored in plants, however, little is known about comparative studies of TLPs within crops. In this study, a comprehensive analysis of TLP genes were carried out in seven crops to explore whether similar function of TLPs in rice could be achieved in other crops. We identified 20, 9, 14, 11, 12, 35, 14 and 13 TLP genes in Glycine max, Hordeum vulgare, Sorghum bicolor, Arabidopsis thaliana, Oryza sativa Japonica, Triticum aestivum, Setaria italic and Zea mays, respectively. All of them were divided into two groups and ten orthogroups (Ors) based on amino acids. A majority of TLP genes had two domains, tubby-like domain and F-box domain, while members of Or5 only had tubby-like domain. In addition, Or5 had more exons and shorter DNA sequences, showing that characteristics of different Ors reflected the differentiated function and feature of TLP genes in evolutionary process, and Or5 was the most different from the other Ors. Besides, we recognized 25 cis-elements in the promoter of TLP genes and explored multiple new regulation pathway of TLPs including light and hormone response. The bioinformatic and transcriptomic analysis implied the stresses induced expression and possible functional redundancy of TLP genes. We detected the expression level of 6 OsTLP genes at 1 to 6 days after seed germination in rice, and the most obvious changes in these days were appeared in OsTLP10 and OsTLP12. Combined yeast two-hybrid system and pull down assay, we suggested that the TLP genes of Or1 may have similar function during seed germination in different species. In general, the results of comprehensive analysis of TLP gene family in multiple species provide valuable evolutionary and functional information of TLP gene family which are useful for further application and study of TLP genes.